La fonología del espa\~nol argentino - Germán Coloma (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2022)
– This paper describes the phonology of Spanish as it is spoken in Argentina. After considering the inventory of phonemes (both consonants and vowels) and their main allophones and phonological rules (including phoneme neutralizations and the use of stress as a distinctive element), there is a description of the most important variations of pronunciation in the different geographic regions of the country. The paper also includes a section about syllable structure, which deals with the admissible combinations of the different phonemes, and with some issues concerning resyllabification (when words are pronounced in the context of connected speech).
Keywords: 330; fonología; espa\~nol; Argentina; fonemas; variación; resilabificación; phonology; Spanish; Argentina; phonemes; variation; resyllabification